2004
DOI: 10.1007/s00520-004-0649-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of opioid-induced bowel dysfunction in cancer patients

Abstract: The gastrointestinal (GI) effects of morphine and other opioids may result in opioid-induced bowel dysfunction (OBD) and the need for treatment. Although OBD is very common in morphine-treated patients, it is usually under-diagnosed. Opioids deliver their GI effect through central and peripheral mechanisms. Laxatives are the pharmaceuticals prescribed most in this area. Prokinetics as well as cholinergic agonists have been used satisfactorily. One-third of patients with OBD have to be treated rectally. The use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 46 publications
1
39
0
9
Order By: Relevance
“…3 Severe adverse effects are often the reason patients discontinue opioid treatment, which naturally results in inadequate pain management. 4,5 As the prescription of opioids has increased several fold in Europe and the US recent years, an increase in adverse effects to opioid treatment has expectedly also developed. 6 Current assessments of OIBD typically rely on self-assessed questionnaires primarily focusing on constipation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Severe adverse effects are often the reason patients discontinue opioid treatment, which naturally results in inadequate pain management. 4,5 As the prescription of opioids has increased several fold in Europe and the US recent years, an increase in adverse effects to opioid treatment has expectedly also developed. 6 Current assessments of OIBD typically rely on self-assessed questionnaires primarily focusing on constipation.…”
Section: Introductionmentioning
confidence: 99%
“…No studies were found in the Brazilian literature systematically evaluating the presence of constipation and the effectiveness of its treatment in children under opioids. Studies with adult patients are useful 15 , however they cannot simply be extrapolated as paradigm for children and adolescents with their own physical, physiological and psychological characteristics. Although the pain control protocol used in this study recommended laxatives when starting with morphine, we have observed that only 36.4% of patients adhered to prescription.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria would include subjective symptoms of constipation (straining and colic), duration, and interference. Objective outcomes, such as the number of stools, character of the stools, radiographic evidence of constipation and family history of constipation should be included [14]. The classification should include complications, such as nausea and vomiting, fissure and rectal prolapse, should be added to number of stools per week as a means of judging severity.…”
Section: Classification Of Constipation: a Research Agendamentioning
confidence: 99%